Innovative Nanoparticle-Based Drug Delivery Systems for Targeted Cancer Therapy - Anggia Folny; Rechny Anbro (Journal of Advanced Pharmaceutical Research Sciences and Sustainability (JAPRSS), 2025)
Background: Targeted cancer therapy aims to maximize therapeutic efficacy while minimizing adverse effects, a challenge often limited by non-specific drug distribution. Nanoparticle-based drug delivery systems have emerged as a promising solution, offering enhanced targeting capabilities and improved drug bioavailability. These innovative systems can deliver therapeutic agents directly to tumor cells, reducing systemic toxicity and improving patient outcomes. Objective: This study aims to evaluate the efficacy and safety of nanoparticle-based drug delivery systems in targeted cancer therapy. The research focuses on the development and testing of various nanoparticle formulations to enhance drug delivery to cancerous tissues while minimizing off-target effects. Methods: A comprehensive experimental approach was employed, including the synthesis of different nanoparticle formulations, in vitro and in vivo testing, and comparative analysis. Nanoparticles were engineered to encapsulate common chemotherapeutic agents and modified with targeting ligands to enhance specificity. In vitro cytotoxicity assays were conducted on multiple cancer cell lines, followed by in vivo studies on tumor-bearing mice to assess biodistribution, therapeutic efficacy, and toxicity. Results: The nanoparticle-based drug delivery systems demonstrated significantly improved targeting and retention in tumor tissues compared to conventional delivery methods. In vitro studies showed enhanced cytotoxicity in cancer cells, with minimal impact on healthy cells. In vivo studies revealed higher tumor accumulation of the drug-loaded nanoparticles, resulting in greater tumor reduction and fewer side effects. Comparative analysis indicated superior performance of targeted nanoparticles over non-targeted formulations. Conclusion: Nanoparticle-based drug delivery systems offer a promising approach for targeted cancer therapy, providing enhanced specificity, reduced systemic toxicity, and improved therapeutic outcomes. These findings support further development and clinical evaluation of nanoparticle formulations to optimize cancer treatment strategies.